William Ayres Galbraith papers - Galbraith, William Ayres
Four ALS (1860 April 20, 22, 27, 29) from Galbraith to his wife discussing the events of the Democratic National Convention in Charleston, S.C. Also, an exchange of letters (1865 April 15, 16) between Galbraith and his wife relating to the assassination of President Lincoln. Includes typewritten abridged copies of all letters.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Assassination